Colonic Strictures after Necrotizing Enterocolitis in Infants: Case Series - Chakya, Vikal Chandra; Agrawal, Chandra Shekhar; Shrestha, Amit Bahadur; Pradhan, Anju; Poudel, Prakash; Sah, Pannalal; Adhikary, Shailesh (Journal of Nepal Paediatric Society, 2011)
The fate of neonates with necrotizing enterocolitis is variable, with colonic strictures being one rare phenomenon after the insult. We describe here two infants with colonic strictures, which developed secondary to neonatal necrotizing enterocolitis. Infants recovered or in the process of recovery after it should be investigated for possibility of development of colonic strictures. Keywords: Colonic strictures; necrotizing enterocolitis; barium enema; stoma DOI: 10.3126/jnps.v31i2.4181 J Nep Paedtr Soc 2010;31(2):127-129